The Relevance of Carok and Settong Dara from a Historical Perspective to Reduce Madura’s Negative Stigma - Nur Baiti Inas Shobiroh; Niken Dia Agustin; Dhinar Mawanti Sauca; Rasendriya Ahmada Maheswara; Riza Oktavia Umami (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Madura is an area in East Java that has a negative stigma from the wider community. This is inseparable from the existence of Carok as a last resort to solve problems for the Madurese people. It is necessary to reconstruct through historiography to reduce the negative stigma. In some previous studies, it examined Carok which was reviewed from the law in Indonesia and the history of the Madurese people to the character of the Madurese people. However, the research has not explained the history of the conflict, especially Carok in Madura. Therefore, researchers use historical methods to explore Carok 's history in detail to know the development of Carok and its relevance to Settong Dara, the values of Carok, and Carok 's understanding of efforts with Settong Dara to reduce negative stigma in Madurese society. The research results obtained are that Carok was known during the Dutch colonial period. At that time, dutch people were moved to challenge the Dutch after the death of Sakera. However, the Dutch fought to make the image of celurit and Madura ugly. Before committing Carok, the two sides in the dispute must first meet the requirements. In the present time, this requirement has been ignored by some people, causing a shift in the meaning of Carok which causes a negative stigma. If examined further, various values in Carok will be known.